PELATIHAN PENGEMBANGAN DIGITALISASI LOCAL WISDOM BERBASIS MOBILE APPS SEBAGAI RINTISAN DESA PANCASILA - Mukhzamilah Mukhzamilah; Ahmad Basri; Imam Marsudi; Subuh Isnur Haryudo; Mohammad Haq (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2022)
Kraton Village, Krian District, Sidoarjo Regency is one of the pioneering Pancasila villages. Krian District borders Balongbendo District which was once the center of the spread of radicalism, precisely in the Islamic Center. This area is one of the places of study that is often filled by Abu Bakar Ba'asyir. The Kraton Village area has also indicated that there are educational institutions that have begun to invite studies whose directions are indicated to influence the community on invitations that lead to a reduction in the sense of nationalism towards the Unitary State of the Republic of Indonesia. The partner's condition is currently in a state of crisis of Pancasila values ​​due to the radicalism that is developing around the partner area. Therefore, it is important for partners to provide more knowledge regarding the importance of Pancasila values ​​in everyday life, but partners also experience obstacles in disseminating information more quickly and effectively to the public due to lack of knowledge about digital technologyThis study aims to provide training on the development of digitalization of local wisdom based on mobile apps which can later be used by the people of Kraton Village to disseminate information related to Pancasila values ​​more effectively and efficiently. The results of the study indicate that training activities are effective in increasing public knowledge about digitalization, and with the development of Mobile Apps, it is effective in increasing the level of public awareness regarding the values of Pancasila.